Optical properties of amorphous hydrogenated and microcrystalline silicon films prepared by plasma enhanced chemical vapor deposition and re-crystallized at moderate temperatures - Netrvalova, Marie; Prusakova, Lucie; Mullerova, Jarmila; Sutta, Pavol (Physica status solidi. C, 2011)
Amorphous hydrogenated silicon films different in thickness (600 – 2400 nm) were deposited by plasma enhanced chemical vapour deposition on Corning glass substrates at 250 °C using silan 10% / argon 90% gas mixture. The samples were consequently isothermally heated in a high temperature vacuum chamber at 0.1 Pa and at temperatures from 580 to 620 °C. In order to evaluate structural and optical properties of the films X‐ray diffraction analysis, Raman spectrometry and optical spectrophotometry were used. Crystalline state (amorphous or microcrystalline), optical band gaps, refractive indices, extinction coefficients, absorption coefficients were determined. X‐ray diffraction analysis indicated that originally deposited films were amorphous with different degree of homogeneity depending on the film thickness. After the heat treatment the films became polycrystalline with crystallite sizes 40‐50 nm without particular dependence on the recrystallization process used. Raman spectrometry confirmed the results obtained from X‐ray diffraction and furthermore revealed the residual amorphous phase 20–25% in volume. Optical spectrophotometry has shown that the values of refractive indices of thermally treated films approach the mono‐crystalline silicon refractive index. Extinction coefficients of the thermally treated films are slightly higher than those for monocrystalline silicon. Absorption coefficients for thermally treated films reached quite high values near the absorption edge of the original amorphous material, which can be advantageous for tandem solar cell technologies. (© 2011 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)